Komunikasi Interpersonal Termediasi Sebagai Strategi Mengurangi Disonansi Kognitif: Studi Kasus Pada Penggemar K-Pop Dalam Pembelian Merch K-Pop Secara Online - Siahaan, Katrin Yemima; Alkhajar, Eka Nada Shofa (Jurnal Komunikasi Massa, 2024)
This study aims to understand how dissonance forms among K-pop fans when purchasing merchandise online and how this dissonance is reduced through mediated interpersonal communication. The research method used in this study is a qualitative approach with a phenomenological perspective, where one or more subjects are examined to understand and experience a phenomenon. The theory used in this study is the Cognitive Dissonance theory. The data collected were analyzed using the data analysis techniques of Miles and Huberman, which include data condensation, data display, verification, and conclusion drawing. The results of the study show that the efforts made by K-pop fans to reduce their dissonance include adding cognitive elements and changing their behavior to achieve consistency. Efforts in the context of mediated interpersonal communication were carried out by communicating with friends and acquaintances of the scammer, in this case, the scammer's friends, using social media platforms such as Line and WhatsApp.